RETRACTION Juhanis, J., Nufus, H., Hermansah, B., Aliriad, H., S, A., Hermansyah, H., & Mortini, A. V. (2025). Optimise The Performance Of Wrestlers: A Comprehensive Strength, Speed And Endurance Programme. Retos, 64. https://doi.org/10.47197/retos.v64.11 - RETOS, RETOS (Retos, 2025)
Juhanis, J., Nufus, H., Hermansah, B., Aliriad, H., S, A., Hermansyah, H., & Mortini, A. V. (2025). Optimise The Performance Of Wrestlers: A Comprehensive Strength, Speed And Endurance Programme. Retos, 64. https://doi.org/10.47197/retos.v64.111245 Article RETRACTED due to bad practices by the authors